Coping With Adolescents Affected by Anorexia Nervosa: The Role of Parental Personality Traits - Monteleone, Alessio Maria; Mereu, Alberta; Cascino, Giammarco; Castiglioni, Maria Chiara; Marchetto, Chiara; Grasso, Melissa; Pontillo, Maria; Pisano, Tiziana; Vicari, Stefano; Zanna, Valeria (Frontiers in Psychology, 2021)
Introduction. Anorexia Nervosa (AN) promotes psychological distress in caregivers who adopt different coping strategies. Dysfunctional caregiving styles exacerbate further distress in the patient promoting the maintenance of the illness. We aimed to assess the possible contribution of caregivers’ personality traits to the adoption of different coping strategies to deal with the affected relative. Methods. Eighty-seven adolescents with AN were recruited. Their parents completed the Family Coping Questionnaire for Eating Disorders and the Temperament and Character Inventory-Revised. Differences between mothers and fathers were assessed through the independent sample t-test. Multivariate regression analyses were run to assess if personality traits, the occurrence of psychiatry conditions in the parents, the marital status and the duration of the illness predicted parental coping strategies. Results. The mothers’ group showed higher levels of avoidance and seeking for information coping strategies than the fathers’ sample. Lower illness duration predicted higher collusion with the illness in both parents. Harm avoidance, cooperativeness and self-directedness positively predicted parental coercion, collusion and seeking for information strategies with some differences between mothers and fathers. Discussion. Illness duration and parents’ personality traits affect the type of parental coping strategies developed to face with AN in adolescents. These variables should be considered in the assessment of families of adolescents with AN and may be addressed to promote more fine-tuned clinical interventions for caregivers.